Calvin and other religions - P. C. Potgieter (Acta Theologica)
Widely differing views on ways leading to true knowledge of God is at present characteristic of discussions in the sphere of religion. Although Calvin worked in a completely different scene, he has laid down certain principles based on his interpretation of Holy Scripture that may contribute to current theological thought on this issue. In this article his views on true and false religion, non-Christian faiths, the uniqueness of Christ as Mediator and Redeemer, and universalism is discussed from the perspective not only of his Institutes, but also of his Commentaries, Tracts and Treatises and Letters. His conviction is that careful observation of God’s Word leads to the principle of Christ as the only way to God. Any kind of self-invented religion, even though it is the result of an appeal by God’s  general revelation on the sensus divinitatis in mankind, leads to idolatry.